HOW DOES THE CAMPUS PARTY CULTURE INFLUENCE STUDENT ACADEMIC PERFORMANCE AND WELBEING? - Ergashova Umida; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract This paper explores the impact of campus party culture on students' academic performance  and  overall  wellbeing.  As  social  gatherings  and  nightlife  activities become increasingly embedded in university life, there is growing concern about their influence on students’ mental health, academic success, and lifestyle choices. Drawing on existing literature and historical perspectives, this study examines how party culture affects  student  behavior,  motivation,  and  time  management,  highlighting  both  the potential benefits and drawbacks. While party culture may foster social bonding and stress  relief,  it  can  also  lead to  academic  decline, poor health  outcomes, and  risky behaviors if not managed properly. This paper aims to provide a balanced view to understand the relationship between partying and the academic and personal lives of university students.